Elimination of SARS-CoV-2 along wastewater and sludge treatment processes. (1st September 2021) - Serra-Compte, Albert; González, Susana; Arnaldos, Marina; Berlendis, Sabrina; Courtois, Sophie; Loret, Jean Francois; Schlosser, Olivier; Yáñez, Adela M.; Soria-Soria, Elena; Fittipaldi, Mariana; Saucedo, Gemma; Pinar-Méndez, Anna; et al.
Highlights: SARS-CoV-2 RNA occurrence was monitored along treatment lines of 16 WWTPs SARS-CoV-2 RNA was frequently detected in wastewater from regions with a high COVID-19 incidence Secondary treatments reduced, MBR and chlorination eliminated SARS-CoV-2 RNA from wastewater SARS-CoV-2 RNA was detected in sludge after thickening and digestion, but not after thermal hydrolysis F-specific bacteriophages could serve as conservative surrogates for SARS-CoV-2 in water treatment Abstract: The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is shed in the feces of infected people. As a consequence, genomic RNA of the virus can be detected in wastewater. Although the presence of viral RNA does not inform on the infectivity of the virus, this presence of genetic material raised the question of the effectiveness of treatment processes in reducing the virus in wastewater and sludge. In this work, treatment lines of 16 wastewater treatment plants were monitored to evaluate the removal of SARS-CoV-2 RNA in raw, processed waters and sludge, from March to May 2020. Viral RNA copies were enumerated using reverse transcriptase quantitative polymerase chain reaction (RT-qPCR) in 5 different laboratories. These laboratories participated in proficiency testing scheme and their results demonstrated the reliability and comparability of the results obtained for each one. SARS-CoV-2 RNA was found in 50.5% of the 101 influent wastewater samples characterized. Positive results were detected more frequently in those regions with a COVID-19 incidence higher than 100 cases per 100, 000 inhabitants. Wastewater treatment plants (WWTPs) significantly reduced the occurrence of virus RNA along the water treatment lines. Secondary treatment effluents showed an occurrence of SARS-CoV-2 RNA in 23.3% of the samples and no positive results were found after MBR and chlorination. Non-treated sludge (from primary and secondary treatments) presented a higher occurrence of SARS-CoV-2 RNA than the corresponding water samples, demonstrating the affinity of virus particles for solids. Furthermore, SARS-CoV-2 RNA was detected in treated sludge after thickening and anaerobic digestion, whereas viral RNA was completely eliminated from sludge only when thermal hydrolysis was applied. Finally, co-analysis of SARS-CoV-2 and F-specific RNA bacteriophages was done in the same water and sludge samples in order to investigate the potential use of these bacteriophages as indicators of SARS-CoV-2 fate and reduction along the wastewater treatment. Graphical abstract: Image, graphical abstract